Elevated serum thyroglobulin levels at the time of ablative radioactive iodine therapy indicate a worse prognosis in thyroid cancer: an Australian retrospective cohort study. (4th August 2016) - Matthews, T J; Chua, E; Gargya, A; Clark, J; Gao, K; Elliott, M
Abstract: Background: Serum thyroglobulin is used as a surrogate marker for well-differentiated thyroid carcinoma recurrence. This study investigates whether thyroglobulin measured at the time of ablative radioactive iodine therapy predicts disease-free survival. Methods: A retrospective review was conducted of patients with well-differentiated thyroid carcinoma presenting from 1989 to 2010 at the Royal Prince Alfred Hospital, New South Wales, Australia. Disease-free survival of patients with a significantly elevated stimulated thyroglobulin level (27.5 µg/l or higher) at the time of ablative radioactive iodine therapy was compared to that of patients without a significantly elevated thyroglobulin level using univariate analysis. Results: Patients with a thyroglobulin level of 27.5 µg/l or higher had an increased relative risk of disease recurrence of 4.50 (95 per cent confidence interval = 1.35–15.04). If lateral neck dissection was required at the time of surgery, patients also had an increased relative risk of macroscopic disease recurrence of 4.94 (95 per cent confidence interval = 1.47–16.55). Conclusion: An elevated thyroglobulin level of 27.5 µg/l or higher at the time of ablative radioactive iodine therapy is a prognostic indicator for macroscopic disease recurrence in well-differentiated thyroid carcinoma.